Barriers to and discourses about breast cancer prevention among immigrant women in Spain: a qualitative study. Issue 11 (18th November 2018) - March, Sebastià; Villalonga, Barbara; Sanchez-Contador, Carmen; Vidal, Clara; Mascaro, Aina; Bennasar, Maria de Lluc; Esteva, Magdalena
Abstract : Objectives: To identify knowledge, barriers and discourses about breast cancer screening in Spain among female immigrants from low-income countries and native Spanish women from a low socioeconomic class. Design: Qualitative interview study with thematic analysis interpreted using cultural mediators. Setting: Mallorca, Spain. Participants: Thirty-six in-depth interviews, using cultural mediators, of immigrant women living in Mallorca who were 50–69 years old and were from Maghreb, Sub-Saharan Africa, Eastern Europe, Latin America, China or were native to Spain and from a low socioeconomic class. Results: We analysed the interviews to assess breast cancer perceptions and beliefs, discourses about breast cancer prevention and barriers to accessing breast cancer prevention programmes. Although the women reported an association of breast cancer with death, they acknowledged the effectiveness of early detection. They also exhibited reluctance to talk about cancer. Discourses about cancer prevention tended to be proactive or fatalistic, depending on the woman's country of origin. For all women, fear of results and lack of time were barriers that limited participation in breast cancer prevention programmes. Language barriers, frequent changes of residence and fear due to status as an irregular (undocumented) immigrant were barriers specific to immigrant women. Conclusions: The culture of origin affects whether an immigrant has a fatalistic or proactive approach toward breast cancer screening. Immigrants from low-income countries and Spanish natives from a low socioeconomic class experience barriers in access to breast cancer screening. Frequently changing homes is also a barrier for immigrant women.